Nutrient removal from domestic wastewater by rapid infiltration system - Tanik, A; Comakoglu, B (ACADEMIC PRESS LTD, 1996)
A wide variety of wastewater treatment processes are available in order to prevent deterioration of the environment. Among these, one of the best, especially for arid and semi-arid regions, is land disposal. In this study, a field model was developed to investigate the removal efficiencies of nutrients, N and P, from domestic wastewater by infiltration through porous media. The model consisted of an inlet chamber, a 25-m long channel and an outlet chamber. The channel was filled with sand type I (d(eff) = 0.55 mm), sand type II (d(eff) = 3.25 mm) and with crushed stone (d(eff) = 10 mm) in turn. N and P removal by infiltration through porous media were investigated with respect to time and distance. The efficiency obtained for N and P removal varied between 50-74% and 46-93%, respectively. The efficiency for both nutrients is reduced with increasing effective size of porous media. (C) 1996 Academic Press Limited
Keywords: adsorption; arid environments; effective size; land disposal; nutrient removal; porous media; WATER; Environmental Sciences & Ecology